Climate and transportation policy sequencing in California and Quebec. Issue 5 (10th August 2021) - Purdon, Mark; Witcover, Julie; Murphy, Colin; Ziaja, Sonya; Winfield, Mark; Giuliano, Genevieve; Séguin, Charles; Kaiser, Colleen; Papy, Jacques; Fulton, Lewis
Abstract: We compare flexible low‐carbon regulations in the transportation sector and their interaction and sequencing with greenhouse gas emissions trading systems in California and Quebec. As momentum builds for greater climate action, it is necessary to better understand how carbon markets and other low‐carbon transportation policies influence one another. First, we demonstrate that emissions trading between California and Quebec has been asymmetric, with linking having little influence on carbon prices from California's perspective but leading to a considerable cost reduction from the point of view of Quebec. Second, we present evidence that Quebec has replicated many of California's low‐carbon transportation policies that promote increased electric vehicle use, where Quebec has an advantage, while deferring to the Canadian federal government with regard to policies that incentivize the production of other low‐carbon transportation fuels. Third, we demonstrate that while the stringency of the policy mix of carbon pricing and flexible transportation regulations has increased over time in both jurisdictions, the stringency of flexible regulations has been more aggressively ratcheted up and is expected to continue to dominate. Overall, our findings suggest that the policy sequence observed in California and Quebec can be attributed to the political economy benefits that the selected instruments confer to governments seeking to move from the middle towards the bottom of the clean technology experience curve. We discuss a number of important research questions and associated hypotheses emanating from our findings, which provide the basis for more in‐depth studies involving a larger universe of cases and economic sectors. Abstract : 我们比较了加利福尼亚州和魁北克省运输部门中灵活的低碳规制以及这些规制与温室气体排放交易系统的互动及排序。鉴于采取更多气候行动的趋势增加，有必要更好地理解碳市场及其他低碳运输政策如何相互影响。第一，我们证明，加利福尼亚州和魁北克省之间的排放交易一直是非对称的，这种交易联系在加利福尼亚州看来对碳价格几乎不存在影响，但从魁北克省看来却导致了大量的成本削减。第二，我们提出证据认为，魁北克省对加利福尼亚州的许多低碳运输政策加以复制，这些政策倡导多使用电子交通工具，这对魁北克省是有利的，同时魁北克省在其他低碳运输燃料生产的激励政策方面听从加拿大联邦政府。第三，我们证明，尽管碳定价和灵活运输规制这一政策组合的严格性在这两个地区都逐渐增加，但灵活规制的严格性一直增加地更为猛烈，并且预计会继续主导该趋势。整体而言，我们的研究发现暗示，加利福尼亚州和魁北克省的政策序列（policy sequence）能归因于政策工具对政府授予的政治经济利益，这些政府试图从清洁技术经验曲线的中部迈向底部。我们探讨了一系列从研究发现中得出的重要研究问题及相关假设，这为更深入地研究更多的案例和经济部门提供了基础。 Abstract : Comparamos las regulaciones flexibles de bajas emisiones de carbono en el sector del transporte y su interacción y secuenciación con los sistemas de comercio de emisiones de gases de efecto invernadero en California y Quebec. A medida que aumenta el impulso para una mayor acción climática, es necesario comprender mejor cómo los mercados de carbono y otras políticas de transporte con bajas emisiones de carbono se influyen entre sí. Primero, demostramos que el comercio de emisiones entre California y Quebec ha sido asimétrico, teniendo la vinculación poca influencia en los precios del carbono desde la perspectiva de California, pero conduciendo a una considerable reducción de costos desde el punto de vista de Quebec. En segundo lugar, presentamos evidencia de que Quebec ha replicado muchas de las políticas de transporte bajas en carbono de California que promueven un mayor uso de vehículos eléctricos, donde Quebec tiene una ventaja, al tiempo que difiere al gobierno federal canadiense con respecto a las políticas que incentivan la producción de otros vehículos de bajo carbono. combustibles de transporte. En tercer lugar, demostramos que si bien la rigurosidad de la combinación de políticas de fijación de precios del carbono y regulaciones de transporte flexible ha aumentado con el tiempo en ambas jurisdicciones, la rigurosidad de las regulaciones flexibles se ha incrementado de manera más agresiva y se espera que continúe dominando. En general, nuestros hallazgos sugieren que la secuencia de políticas observada en California y Quebec puede atribuirse a los beneficios de economía política que los instrumentos seleccionados otorgan a los gobiernos que buscan moverse desde el centro hacia el final de la curva de experiencia de tecnología limpia. Discutimos una serie de preguntas de investigación importantes e hipótesis asociadas que emanan de nuestros hallazgos, que proporcionan la base para estudios más profundos que involucran un universo más amplio de casos y sectores económicos.